Community Attitude About the Effects of Corruption on Forest Governance--A Case of Malakand District of Khyber Pakhtunkhwa Pakistan - Taimoor Khalid; Asad Ullah; Mussawar Shahand; Nayab Ali (NUST Journal of Social Sciences and Humanities, 2021)
This research paper focused on finding links between poor forest governance and corruption. A sample size of 357 respondents was proportionally allocated to each union council and then randomly selected. Chi-square test was used to test the association between the variables. The result shows that forest governance had a significant association with the power elite get illegal management benefits from the forest (P=0.000). Moreover, the political influence on the distribution of benefits received from forest productivity was found significantly associated with forest governance, in addition, the association of the inter-connection of corruption mafia was found significant (P=0.000) with forest governance. Depoliticizing the forest department, establishing rule of law and implementation of the laws in its true spirit without any discrimination can improve forest governance.